THE IMPLEMENTATION OF CONTEXTUAL TEACHING AND LEARNING (CTL) IN TEACHING ENGLISH SPEAKING SKILL : A Case Study of Eight Grade Students in a Junior High School - Nengsih, Rahayu (2015)
This thesis reports a study on the implementation of Contextual Teaching and Learning (CTL) to teaching speaking by a teacher in one private junior high school in Bandung. The study intends to portray the efforts made by the teacher in the classroom when teaching speaking through CTL and to report the students' responses. Therefore, this study aims to describe how speaking skill is taught through CTL, to investigate teacher's opinion about the implementation of CTL in teaching speaking and to find out the students difficulties in the speaking class through CTL. The study employed a qualitative case study research design. The data were obtained from observation, interview and questionnaire. The findings revealed that the teaching and learning process in implementing the components of CTL method (Making meaningful connection, Doing significant work, Self-regulated meaning, Collaborating, Critical and creative thinking, Nurturing the individual, Reaching the high standard and Using authentic assessment) is effective enough, especially in improving students' English speaking skill in transactional and interpersonal conversation. Based on the teacher's interview, it is suggested that CTL method is also very good for junior high school students because there are many advantages; (1) students were easy to absorb the academic material; (2) the student got meaning from the academic material;(3)It helps the students to construct their speaking; (4) it provides ways for students to discuss and interact with their friends; (5) it helps the students to solve the problems. However, the students still have difficulties in speaking class. Based on the findings and the discussion, it is recommended that teachers should more focus on their students' difficulties and reluctant to speak English. In addition, teachers are suggested to keep implementing the CTL method to help students easily catch the academic material and retain the knowledge in their mind for a long time.